Aboriginal Biocultural Knowledge in South-eastern Australia: Perspectives of Early Colonists. By Fred Cahir, Ian D. Clark, and Philip A. Clarke. 2018. Csiro Publishing, Clayton, Australia. 334 pp. - Svanberg, Ingvar (Ethnobiology Letters, 2021)
N/A